Diferentes lâminas de água e doses de nitrogênio na produção de pimentão - Cavalcante, Regina Régia Rodrigues (2008)
The work was carried of objective to weigh the effect of differents shots of nitrogen and water blades on the producti on in pepper (Capsicum annuum L.). The study was carrid out in the experimental area of Laboratory of Hydraulic and Irrigation of Departament of Agricultural Engineering of Universidade Federal do Ceará, in Campus do Pici, Fortaleza, Ceará. The work was executed from august 2007 to january 2008, grow Cascadura Ikeda (TopSeed) cultivated in field. The irrigation system used was drip-irrigation, and 0,5 m between plants. The seedlings production were in polystyrene tray of 128 cells and planted in 40 DAS, at 0,8 m x 0,5 m spacing. The experimental arrangement is in lane, with 4 plots. The treatments were used: 4 blade irrigation (L1, L2, L3 and L4) and 4 shots of nitrogen (N1, N2, N3 and N4). The blades irrigation was joint in evaporation of on a class “A” pan corresponding to 50%, 75%, 100% e 125% of daily evaporation on a class “A” pan (ECA, mm day-1) and the shots of nitrogen to be joint in recommendation of fertilizacion to pepper in Ceará correspond to 8g of N plant-1, the shots to divided in 6, 8, 10 e 12g of N plant-1 equivalent to (150, 200, 250 and 300 kg of N ha-1). To carried daily irrigations and the harvests after 64 DAT, to carried weekly. To valued the variables: number of fruit, average length of fruit, average weigth of fruit and yield. The aplication of different blades of water and different shots of nitrogen did not influence for the variables: number of fruit, average length of fruit and yield. Only to the variable average weigth of fruit relationship the blade of irrigation x nitrogen was signicative L4 N1 the treatment with biggest average weigth of fruit.